2010
DOI: 10.1128/aem.01968-09
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Characterization of Shiga Toxin-Producing Escherichia coli and Other Potentially Diarrheagenic E. coli Strains in Retail Meats

Abstract: To determine the presence of Shiga toxin-producing Escherichia coli (STEC) and other potentially diarrheagenic E. coli strains in retail meats, 7,258 E. coli isolates collected by the U.S. National Antimicrobial Resistance Monitoring System (NARMS) retail meat program from 2002 to 2007 were screened for Shiga toxin genes. In addition, 1,275 of the E. coli isolates recovered in 2006 were examined for virulence genes specific for other diarrheagenic E. coli strains. Seventeen isolates (16 from ground beef and 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 55 publications
2
47
3
2
Order By: Relevance
“…Independently of the method employed, in this study the STEC prevalence resulted to be higher than what has been previously reported (Brooks et al, 2001;Doyle and Schoeni, 1987;Fantelli and Stephan, 2001;Pradel et al 2000;Xia et al, 2010). This could be attributed to the different experimental approaches employed for the detection but also to the different types of foodstuffs considered.…”
Section: Discussioncontrasting
confidence: 55%
“…Independently of the method employed, in this study the STEC prevalence resulted to be higher than what has been previously reported (Brooks et al, 2001;Doyle and Schoeni, 1987;Fantelli and Stephan, 2001;Pradel et al 2000;Xia et al, 2010). This could be attributed to the different experimental approaches employed for the detection but also to the different types of foodstuffs considered.…”
Section: Discussioncontrasting
confidence: 55%
“…Furthermore, although the contamination rate of mutton in this study (13.3%) was lower than the results reported in Iran (35.4%; and New Zealand (17%; Brooks et al, 2001), it was higher than the rate observed in previous investigation in Italy (7.1%; Franco et al, 2009). In addition, according to the results chicken feet showed higher contamination than chicken meat, whereas previous investigations represented lower rate of contamination with STEC in chicken meat and products (Xia et al, 2010;Bai et al, 2015). Isolation of STEC from chicken meat and products represented that in addition to ruminant's meat as the major source of STEC, poultry meat may be another reservoir of contamination with this pathogen (Dipineto et al, 2006).…”
Section: Discussionmentioning
confidence: 77%
“…PCR amplification to detect the presence of Shiga toxin genes stx 1 and stx 2 was performed using published primers (43). Briefly, a 25-l PCR amplification mixture containing 1ϫ PCR buffer (Promega), 0.1 mM each dNTP (Life Technologies), 2.5 mM MgCl 2 , 0.5 M each primer (Integrated DNA Technologies, Coralville, IA), 1.25 U of GoTaq Hot Start polymerase (Promega), and 2 l of DNA template was amplified in a C1000 Touch thermal cycler (Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%